Intimate coupling of photocatalysis and biodegradation for wastewater treatment: Mechanisms, recent advances and environmental applications. (15th May 2020) - Yu, Mingliang; Wang, Jiajia; Tang, Lin; Feng, Chengyang; Liu, Haoyu; Zhang, Hao; Peng, Bo; Chen, Zhaoming; Xie, Qingqing
Abstract: Due to the increase of emerging contaminants in water, how to use new treatment technology to make up for the defects of traditional wastewater treatment method has become one of the research hotspots at present. Intimate coupling of photocatalysis and biodegradation (ICPB) as a novel wastewater treatment method, which combines the advantages of biological treatment and photocatalytic reactions, has shown a great potential as a low-cost, environmental friendly and sustainable treatment technology. The system mainly consists of photocatalytic materials, porous carriers and biofilm. The key principle of ICPB is to transform bio-recalcitrant pollutants into biodegradable products by photocatalysis on the surface of porous carriers. The biodegradable products were mineralized simultaneously through the biofilm inside the carriers. Because of the protection of the carriers, the microorganism can remain active even under the UV-light, the mechanical force of water flow or the attack of free radicals. ICPB breaks the traditional concept that photocatalytic reaction and biodegradation must be separated in different reactors, improves the purification capacity of sewage and saves the cost. This review summarizes the recent advances of ICPB photocatalysts, carriers and biofilm being applied, and focuses on the mechanisms and reactor configurations which is particularly novel. Furthermore, the possible ongoing researches on ICPB are also put forward. This review will provide a valuable insight into the design and application of ICPB in environment and energy field. Graphical abstract: Image 10454 Highlights: The synergistic adsorption, photocatalysis and biodegradation in ICPB are discussed. Mechanisms of self-regulation, co-substrate and competition are discussed. Recent advances of photocatalyst types, carriers and biofilms in ICPB are summarized. Advantages and disadvantages of different PCBBR configurations are summarized. ICPB applications in treatment of wastewater and energy production are introduced.